2023
DOI: 10.1002/gcc.23129
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor‐type TERT mutations associated with recurrence in ovarian clear cell carcinoma

Abstract: Several cancers harbor "enhancer-type" mutations of the telomerase reverse transcriptase (TERT) promoter for immortalization. Here, we report that 8.6% (8/93) of ovarian clear cell carcinomas (OCCCs) possess the "suppressor-type" TERT promoter mutation. The recurrence rate of OCCCs with "suppressor-type" TERT promoter mutations was 62.5% (5/8) and was significantly higher than that of the "unaffected-type" with no mutation (20.8%, 15/72) or "enhancer-type" TERT promoter mutations (7.7%, 1/13). Our findings sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…(Yoo H, 2023) A similar conclusion from Irshaid et al reported that a TERTp mutation could be further strati ed as high-risk OCCC in the no speci c molecular pro le subgroup (Irshaid, Costigan et al, 2023). In contrast to the above research, Kobayashi et al reported that the progression-free survival rate of the "enhancer-type" group including the hotspot mutations of TERTp was signi cantly longer than that of the wild-type and "suppressor-type" (with uncommon mutations) mutation groups (Kobayashi et al, 2023). While no signi cant difference in disease-speci c overall survival was observed between patients with and without TERTp hotspot mutations in the cohorts of Nishikimi et al and Wu et al(Nishikimi et al, 2018, Wu et al, 2014 In our study, patients with the − 124C > T mutation had longer PFS and OS than those with wild-type.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…(Yoo H, 2023) A similar conclusion from Irshaid et al reported that a TERTp mutation could be further strati ed as high-risk OCCC in the no speci c molecular pro le subgroup (Irshaid, Costigan et al, 2023). In contrast to the above research, Kobayashi et al reported that the progression-free survival rate of the "enhancer-type" group including the hotspot mutations of TERTp was signi cantly longer than that of the wild-type and "suppressor-type" (with uncommon mutations) mutation groups (Kobayashi et al, 2023). While no signi cant difference in disease-speci c overall survival was observed between patients with and without TERTp hotspot mutations in the cohorts of Nishikimi et al and Wu et al(Nishikimi et al, 2018, Wu et al, 2014 In our study, patients with the − 124C > T mutation had longer PFS and OS than those with wild-type.…”
mentioning
confidence: 87%
“…Ayhan et al, 2014) Another study reported that the TERTp hotspot mutations (-124C > T and − 146C > T) had a higher promoter activity than the wild-type, and the promoter activity of the uncommon site mutations was the lowest (Kobayashi, Nishikimi et al, 2023). Furthermore, TERT expression increased with tumor grade and stage (Maraei, Hatta et al, 2012).…”
mentioning
confidence: 99%